Strategies for Enhancing Creative Competencies in Visual Arts for 5th–7th Grade Students - Tog‘aev Keldiyor Xamidovich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This article explores strategies for enhancing creative competencies in visual arts lessons for students in grades 5–7. It emphasizes the development of students’ imagination, creative thinking, and problem-solving skills through interactive learning, collaborative activities, and the use of diverse artistic materials. The study provides practical recommendations for implementing these strategies in classroom settings to foster students’ creativity, engagement, and holistic development.